Implementasi Pendidikan Seks pada Anak Usia Dini - Fajrin, Latifah Permatasari; Subar Junanto; Kurniasari, Diyah (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2020)
The problem in this research is the lack of knowledge of sex in early childhood and the methods used by educators in sex education are too monotonous in learning. The purpose of this study was to determine the process of sex education in TK IT AL-Muhlas Yusro. This research use desciptive qualitative approach. This research was conducted at TK IT AL Muhlas Yusro. Sawit, Boyolali, Central Java from June to December 2019. The subjects of this study were teachers. The informants of this research are: Kindergarten Head and students. Data is collected by observation, interview and documentation. The validity of the data is obtained using source and method triangulation. The collected data is then analyzed by the stages of data reduction, data presentation, and drawing conclusions. The implementation of sex education includes teacher preparation, namely preparing RPPH as a preliminary guide before learning in class. Implementation of learning with the storytelling method which consists of three processes namely opening, core activities, and closing. Evaluation is carried out through several stages, among others, observation of students' activities, children's work, and analysis of developments seen in children's behavior. Sex education is considered quite successful even though there are still shortcomings such as the lack of media, different children's understanding and minimal parental participation when at home. Keywords: Implementation, Sex Education, Early Childhood